The Arctic Oscillation predicts effects of climate change in two trophic levels in a high‐arctic ecosystem - Ronny Aanes; Bernt‐Erik Sæther; Fiona M. Smith; Elisabeth J. Cooper; Philip A. Wookey; Nils Are Øritsland (Ecology Letters, 2002)
During recent decades there has been a change in the circulation of atmospheric pressure throughout the Northern Hemisphere. These variations are expressed in the recently described Arctic Oscillation (AO), which has shown an upward trend (associated with winter warming in the eastern Arctic) during the last three decades. We analysed a 12‐year time series on growth of Cassiope tetragona (Lapland Cassiope) and a 21‐year time series on abundance of a Svalbard reindeer population. High values of the AO index were associated with reduced plant growth and reindeer population growth rate. The North Atlantic Oscillation index was not able to explain a significant proportion of the variance in either plant growth or reindeer population fluctuations. Thus, the AO index may be a better predictor for ecosystem effects of climate change in certain high‐arctic areas compared to the NAO index.